Exploring Differentiated Learning: A Teaching at the Right Level Approach in Elementary Schools - Putri, Arizkylia Yoka; Muldash, Mimyn Putri (Journal for Lesson and Learning Studies, 2024)
The gap in learning outcomes between students with different levels of ability is a complex challenge in the world of education. Differentiated learning is a solution to accommodate individual student differences. The primary objective of this research is to evaluate the effectiveness of the Teaching at the Right Level (TaRL) approach in enhancing students' understanding of data processing material, employing high-level operational verbs such as 'evaluate,' 'analyze,' and 'synthesize.' This research involved class teachers and 30 class 6A students. Data collection techniques included interviews, observation, and documentation of student learning outcomes. Data analysis was conducted through stages of data collection, data reduction, data display, and drawing conclusions. The research findings indicate that the TaRL approach significantly improves students' comprehension of data processing material. However, to address challenges in implementation, a more focused strategy and comprehensive support are necessary. The study concludes that strengthening the differentiated learning approach using TaRL in the elementary school curriculum, with robust support from schools, parents, and the government, is crucial for its success.